Minat Pembelian Ulang Pada Gen Z : Peran Keamanan, Pengalaman, Kepuasan dan Kepercayaan Pada Pengguna Shopee - Damayanti, Silvia; Pakarti, Piji; Aryanto, Vincent Didiek Wiet; Aqmala, Diana (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
The rapid development of digitalization has changed people's shopping behavior, with Indonesia's e-commerce transactions reaching Rp689 trillion by 2024. With an internet penetration rate dominated by Gen Z at 87%. Shopee, as one of the most popular e-commerce platforms, needs to attract and retain the potential Gen Z market segment. However, security risks that affect trust and unsatisfactory customer experience make people hesitant in making online transactions. As competition intensifies, it becomes important for e-commerce platforms to retain customers and encourage repeat purchases. This study aims to analyze the effect of security, consumer experience, satisfaction and trust on consumer repurchase intention using the Shopee platform. Using a quantitative approach, data was collected through questionnaires from 156 respondents aged 17-27 years old in Kudus City. The research findings reveal that safety influences satisfaction and trust, while experience also influences satisfaction and trust. In addition, satisfaction and trust influence interest in repurchase intentions. These results underscore the importance of improving user safety, experience, satisfaction, and trust in maintaining consumer engagement on Shopee. Future research should explore additional variables to provide a more comprehensive understanding of the factors that influence online shopping behavior.